Neurofibromatosis type 1 associated with coarctation of the abdominal aorta - Reema Al Essa; Mohammed Al Jasser (PAGEPress Publications, 2021)
Neurofibromatosis type 1 (NF1) is one of the most autosomal dominant genetic disorders. NF1 vasculopathy is a rare complication of NF1 with prevalence up to 6% including aneurysms, arterial stenosis, aorta coarctation and arteriovenous malformations [...]